Antiphase boundary in antiferromagnetic multiferroic LuMn0.5Fe0.5O3: anomalous ferromagnetism, exchange bias effect and large vertical hysteretic shift. (6th July 2018) - Sarkar, Tanushree; Reddy, V Raghavendra; Elizabeth, Suja; Kumar, P S Anil
Abstract: The emergence of exchange bias effect in Fe3 O4 thin films has been since attributed to the presence of anti phase boundary (APB) growth defects despite lack of direct experimental evidence. In the present report, APB induced anomalous weak ferromagnetism and exchange bias property of single-phase antiferromagnetic (AFM) system LuMn0.5 Fe0.5 O3 (LMFO) is discussed and 57 Fe Mössbauer spectroscopy and high resolution transmission electron microscopy (HRTEM) measurements are used to probe the origin of the observed effect. In addition to the sextet component corresponding to the long range AFM ordering, the measured Mössbauer spectra reveal the presence of a small component (10%–12%) near zero velocity with unusually small internal field. This indicates the presence of APB defects. From micro structural investigations using HRTEM, presence of APB type defects and dislocations are confirmed. In addition to the exchange bias effect, upon field cooling, hysteresis loop exhibits large vertical shift due to strong pinning effect of the APB. Finally we further annealed the optimally sintered sample LMFO and studied the evolution of defects, and their influence on weak ferromagnetism and exchange bias properties. Our present experimental findings may pave the way in creating new functionalities in materials using APB-type growth defects.